Patients with melanoma treated with immune checkpoint inhibitors who had non-thyroid endocrine and skin immune-related adverse events have better prognosis: A systematic review and meta-analysis - Sun, Qian; Sun, Hongyan; Wu, Nan; Hu, Yue; Zhang, Fangqing; Cong, Xianling (Frontiers in Oncology, 2022)
Background: Several studies have reported an association between the occurrence of immune-related adverse events (irAEs) and prognosis in patients with melanoma treated with immune checkpoint inhibitors (ICIs), but the results remain controversial. We conducted a systematic review and meta-analysis to investigate the association between irAEs and survival in patients with melanoma treated with ICIs. Methods: We searched the PubMed, Web of Science, and China National Knowledge Infrastructure databases through May 5, 2022 for clinical studies evaluating the association between irAEs and in melanoma patients treated with ICIs. Combined hazard ratios (HRs) for overall survival (OS) and progression-free survival (PFS) were calculated using fixed- or random-effects models based on heterogeneity. This study is registered on PROSPERO, number CRD42022338308. Results: A total of 60 articles were included, with 16,520 patients. In patients with melanoma treated with ICIs, the occurrence of irAEs was significantly associated with better OS (HR, 0.58; 95% confidence interval [CI], 0.51–0.66; P<0.00001) and PFS (HR, 0.61; 95%CI, 0.51–0.72; P<0.00001). Endocrine irAEs (OS, HR, 0.81; 95%CI, 0.72–0.92; P=0.001; PFS: HR, 0.84; 95%CI, 0.73–0.96, P=0.009), skin irAEs (OS, HR, 0.59; 95%CI, 0.41–0.85; P=0.004; PFS: HR, 0.43; 95%CI, 0.36–0.52; P<0.00001), vitiligo (OS, HR, 0.22; 95%CI, 0.15–0.31; P<0.00001; PFS, HR, 0.33; 95%CI, 0.25–0.44; P<0.00001), and grade 1–2 irAEs (OS, HR, 0.67; 95%CI, 0.58–0.78; P<0.00001; PFS, HR, 0.62; 95%CI, 0.51–0.76; P<0.00001) showed similar results. However, thyroid, lung, gastrointestinal, liver, and grade 3–4 irAEs were not significantly associated with OS and PFS. The occurrence of non-thyroid endocrine irAEs was significantly associated with better OS (HR, 0.22; 95%CI, 0.15–0.31; P<0.00001). In patients with melanoma treated with anti-programmed cell death protein 1 (OS, HR, 0.61; 95%CI, 0.51–0.72; P<0.00001; PFS, HR, 0.59; 95%CI, 0.47–0.74; P<0.00001), the association between irAEs and clinical benefit was clearer than in patients treated with anti-cytotoxic T-lymphocyte-associated protein 4 (OS, HR, 0.68; 95%CI, 0.52–0.89; P=0.005; PFS, HR, 0.93; 95%CI, 0.49–1.78; P=0.83). Conclusion: Among patients with melanoma treated with ICIs, those who developed non-thyroid endocrine irAEs and cutaneous irAEs have better prognosis. This suggests that non-thyroid endocrine irAEs and cutaneous irAEs may be a prognostic biomarker for patients with melanoma treated with ICIs.